Sleep deprivation of working adolescents—a hidden work hazard - Teixeira, Liliane R; Fischer, Frida M; Lowden, Arne (Scandinavian Journal of Work, Environment & Health, 2006)
This manuscript discusses the sleep deprivation of adolescents and young workers and its impact on their work and learning. Several studies have shown that working adolescents wake up earlier, have a shorter nocturnal sleep duration and a higher level of sleepiness during wake time during the week than nonworking students do. These studies indicate that working students may have their learning ability negatively affected by being tired and sleepy. Therefore, on the basis of these results, the authors recommend that educational programs geared to sleep hygiene should be one of the priorities of the curriculum. At the same time, the workhours of teenagers should be shortened in order to allow them to work and study during daytime and to have enough time at night for leisure and rest. These recommendations would improve the quality of life of the population that already is or will soon be participating in the job market.
Keywords: child labor; educational program; opinion; sleep deprivation; sleep hygiene; teenage worker; work hazard; workhours; working adolescent